Two new species of Bursera (Burseraceae) from Mexico - Rzedowski, Jerzy; Calderón De Rzedowski, Graciela (Instituto de Ecología, A.C., 2006)
Bursera madrigalii, from the state of Michoacán, and B. simplex, from the state of Oaxaca, both belonging to section Bullockia, are described as new and illustrated. The leaves of B. madrigalii are similar to those of B. hintonii Bullock, but its reproductive morphology indicates a closer relationship with B. xochipalensis Rzed. B. simplex has simple leaves and seems to be related to B. infernidialis Guevara & Rzed. and perhaps to B. biflora (Rose) Standl.